Spatial patterns of accessibility between islands of the North and South Aegean regions and Attica - Kavroudakis, Dimitris; Polydoropoulos, Ioakeim; Kyriakidis, Phaedon; Kizos, Thanassis (My University, 2018)
Accessibility is an important determinant of socio-economic development at all spatial levels because it critically affects the operations and success of economic activities. Measures of accessibility are frequently used to support development policy-making and spatial planning. The spatial sciences provide several quantitative approaches to assess accessibility and identify over- and under-served areas. This chapter contributes to the broader issue of quantifying accessibility by analyzing the spatial patterns of accessibility in the case of a very fragmented geographical space; the islands of the North and South Aegean Sea Regions, Greece. Following a preliminary spatial analysis of: Transportation route frequency, passen-gers/population, two graph theory metrics and mean ticket cost, clustering methods, enhanced by introducing local indices of spatial association, are employed to determine possible groupings of islands and delineate spatial clusters based on their accessibility. "Hot spots" of accessibility in the study area are identified, suggesting that accessibility is more spatially clustered than would be expected under a random model.
Keywords: Spatial analysis; Spatial clustering; Region-building; Spatial association